NOVELTY DOES MATTER: SLM IS A CONVENIENT WAY FINDING A RESEARCH ORIGINALITY - Winda Nur Cahyo (Journal of Industrial Engineering Management, 2021)
A good research is a research with a clear research novelty of research originality. However, finding the novelty or originality is one of the most challenging process in research in any field.  Although there are many proposed models to assist researchers and scholars to determine research novelty-such as Systematic Literature Review, K-Chart, Card System, Decision Tree, Mind Mapping- most of the tools or models fail to fulfill the need of some researcher to effectively present the complex result of literature review. To deal with this obstacle, a new tool named SLM (Systematic Literature Mapping) is proposed in this article in order to visually present the result of a complex literature review in the form of a decision tree that leads to an effective and efficient literature review process. The newly proposed model combines SLR (Systematic Literature Review), an established-well-known tool for literature review with a model named K-Chart. To verify the proposed model, a case study is discussed to accompany the example of the application of this new tool. The case study is finding the research opportunity of the application of big data in the industry.  The result shows that SLM is capable to serve its purpose in the process of literature review